2004
DOI: 10.1093/jb/mvh062
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Properties of Pierisin-1 and Its N-Terminal Domain, a Guanine-Specific ADP-Ribosyltransferase from the Cabbage Butterfly

Abstract: The cabbage butterfly, Pieris rapae, produces an ADP-ribosylating cytotoxic protein, pierisin-1. Unlike other ADP-ribosylating toxins, the acceptor site for ADP-ribosylation by pierisin-1 is the N-2 position of guanine bases in DNA. The present study was designed to characterize this novel guanine-specific ADP-ribosyltransferase, pierisin-1. The N-terminal polypeptide from Met-1 to Arg-233, but not the C-terminal Ser-234-Met-850 polypeptide, was found to exhibit guanine ADP-ribosyltransferase activity. Trypsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…NAD + (K M = 45 lM; k cat = 0.04 s À1 ) (Schirmer et al, 2002a) show a somewhat greater affinity but a far lower turnover for this substrate under the experimental conditions than those reported for the related ADP-ribosyltransferase pierisin (K M = 170 lM; k cat = 55 s À1 ) (Watanabe et al, 2004).…”
Section: Mtx1mentioning
confidence: 55%
“…NAD + (K M = 45 lM; k cat = 0.04 s À1 ) (Schirmer et al, 2002a) show a somewhat greater affinity but a far lower turnover for this substrate under the experimental conditions than those reported for the related ADP-ribosyltransferase pierisin (K M = 170 lM; k cat = 55 s À1 ) (Watanabe et al, 2004).…”
Section: Mtx1mentioning
confidence: 55%
“…KC456421; ERIC1_1c00040) is a single-chain AB toxin and belongs to an enigmatic family of toxins [31], so far comprising only few members, the larvicidal toxin MTX1 expressed by Lysinibacillus sphaericus and several pierisin-like toxins expressed by Pieridae , a large family of butterflies [32], [33]. It has been proposed that Plx1 has ADP ribosyltransferase activity [31] as already shown for MTX1 and pierisin-1 [32], [33]. Plx2 was shown to be a binary AB toxin with two separate ORFs encoding the A and B subunits [31].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the DNA ADP-ribosylating activity of purified pierisin-1 in solution at pH 9.0 decreases to around half for 42 h at 37 °C. 16) In the bodies of butterflies after killing, it is assumed that degradation of pierisin-1 might be suppressed by coexistence with other substances. We are now examining cytotoxicity and DNA ADP-ribosylating activity of crude extracts from various Pieridae butterflies obtained from many other countries.…”
Section: Resultsmentioning
confidence: 99%